Effectiveness of Legal Aid For The Poor Communities of Makassar City - Rinaldy Bima, Muhammad (Universitas Ekasakti, 2023)
This research aims to find out and analyze what factors influence the implementation of legal assistance for the poor in the city of Makassar. This research uses empirical research methods using data collection methods and studying legal assistance. Then data is obtained from interviews and observations to produce what is expected and conclusions about the problem. The results of this research show that there are factors that influence the implementation of legal assistance for the poor in the city of Makassar. The legal factor itself (law) where the implementation of legal aid itself must be clear in accordance with applicable law. The factor of law enforcement officers/enforcers is very influential in the judicial process in order to assist in the process of implementing legal aid. Community factors in order to be able to help the community in legal aid as a system of institutions or apparatus/law enforcement should pay more attention to several things, for example: providing legal education to people who are not legally competent so that they know more, providing legal counseling